EVALUASI DAN POTENSI PENGOPERASIAN BUS SEKOLAH (STUDI KASUS : BUS HALOKES KOTA MALANG) - Tony Prasetyo; Ludfi Djakfar; Sobri Abusini (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2015)
EVALUASI DAN POTENSI PENGOPERASIAN BUS SEKOLAH (STUDI KASUS : BUS HALOKES KOTA MALANG)Evaluation And Potential Operation Of School Bus(Case Study: Bus Halokes Poor Town)Tony Prasetyo1, Ludfi Djakfar2, Sobri Abusini31,2,3 Jurusan Teknik Sipil, Fakultas TeknikUniversitas BrawijayaAlamat korespondensi : Jln. MT. Haryono, Malang, Jatimemail: tony_ayu@yahoo.co.idAbstractMalang is a city with a high population density about 8129 people /km2. Malang city is known as a tourism and educational city. The high population and many activities causes a traffic jam in Malang. To reduce the traffic jam and help students reduce using private motorcycle, Malang goverment provide some free school bus for students. The method used in this research is descriptive quantitative analysis with the description of public transport operational performance analysis and analysis of vehicle operating costs. It also used SWOT method to determine the performance of the school bus, potential, problems and strategies used to develop a school bus. The results showed that operational performance is good with load factor value less than 1 every segment. The travel speed average is 40 km / hour about 40 until 60 minutes. The service time is about two times in every morning and afternoon and the waiting time of passengers between 5 to 10 minutes. The results of BOK calculation is Rp145.579,- a day which is subsidized by the government of Malang city. Based on the user’s perception of school buses, the most important factors considered are comfort, safety and reliability. Based on SWOT calculations, the development strategy contained in a space that is rapid growth strategy that harnesses the strength and the opportunities.Keyword : School buses, operational performance, BOK, SWOT, development strategyAbstrakKota Malang merupakan kota dengan kepadatan penduduk yang tinggi mencapai 8.129 jiwa/km2. Selain sebagai kota wisata, kota Malang juga dikenal sebagai kota pendidikan. Tingginya kepadatan penduduk Kota Malang sejalan dengan beragamnya aktifitas yang ada menyebabkan terjadinya kemacetan di Kota Malang. Untuk mengurangi kemacetan dan membantu pelajar mengurangi penggunaan kendraan pribadi, pemerintah Kota Malang menyediakan bus sekolah gratis bagi para pelajar. Penelitian ini bertujuan untuk Evaluasi kinerja bus sekolah menggunakan metode Analisis Deskriptif serta analisis biaya operasional kendaraan serta metode SWOT untuk mengetahui kinerja dan strategi. Hasil penelitian menunjukkan bahwa kinerja operasional kendaraan cukup baik dengan nilai load factor kurang dari 1 per segmen dengan kecepatan perjalanan rata-rata 40 km/jam dan waktu tempuh 40-60 menit. Waktu pelayanan 2 kali yakni berangkat dan pulang sekolah dengan waktu tunggu penumpang antara 5 sampai 10 menit. Sementara itu hasil perhitungan BOK adalah Rp 145.579,- per hari yang disubsidi pemerintah. Berdasarkan persepsi pengguna bus sekolah kenyamanan, keamanan dan keandalan adalah faktor yang dirasa paling penting. Berdasarkan hasil perhitungan SWOT, strategi pegembangan terdapat pada ruang A yaitu rapid growth strategy yakni strategi pertumbuhan cepat dengan memanfaatkan kekuatan dan peluang yang ada.Kata Kunci : Bus sekolah, kinerja operasional, BOK, SWOT, strategi pengembangan